Policy Complements to the Strengthening of IPRS in Developing Countries - Cavazos Cepeda, Ricardo H.. (OECD Trade Policy Papers, 2010)
The past two decades have witnessed an active period of global reform with respect to policies concerning Intellectual Property Rights (IPRs). This paper examines - from an empirical, economic perspective - policies that complement the generally strengthened framework for IPRs in developing countries. The analytical approach involves three complementary levels of analysis: macro, micro and country case studies. Across all three approaches, the results point to a tendency for IPR reform to deliver positive economic results. Reforms concerning patent protection have tended to deliver the most substantial results, but the results for copyright reform and trademark reform were also positive and significant. Overall, the policy complements that were found to be most important in facilitating positive results were those related to inputs for innovative and productive processes and to the ability to conduct business. These include policies that influence the macro-environment for firms as well as the availability of resources (e.g. related to education), the legal and institutional conditions and the fiscal incentives